Stratifikasi Sosial dalam Sistem Perekonomian Masyarakat Urban - Siska Wahyuni Fitri; Aulia Rahman; Nelfia Nofitri; Januar Januar (Concept: Journal of Social Humanities and Education, 2023)
Social stratification is the grouping of a society into certain classes. Where this grouping can show differences in status that exist in society. Every society has something that is valued, maybe in the form of money, maybe land, maybe objects of economic value, maybe also in the form of power, knowledge, piety in religion, or descent from certain families, occupations and others. It is well known that education and the learning process are very important needs in human life. Therefore, this study aims to determine the form of social stratification in the economy of urban communities. The researcher used a qualitative descriptive method. The results show that those with low socio-economic status tend to have high social relationships while those with high socio-economic status tend to have relatively low relationships. In other words, what influences the pattern of social interaction or social relations in urban communities is socioeconomic status, type of work, income level and education level. In addition, there are other factors that determine the pattern of social interaction or social relations in the city.